The Possibility of Applying Religious Multiculturalism Policy in Local Government in Indonesia - Nisa, Khoirun (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
This study investigates local government’s opportunities for implementing religious multiculturalism policies, which refer to the regional autonomy system. The subject of this research is Tangerang City, Banten Province, which has an urban and pluralistic image of society due to its location as a buffer for the city capital. Data collection in this study used a qualitative method which refers to in-depth interviews of 15 respondents who came from representatives of the government and religious leaders. In addition, secondary data in this study relates to observations, field notes, documentation, and relevant literature. The result of this study indicates several indicators that lead to the possibility for Tangerang City’s local government to apply a religious multiculturalism policy: government institutions in strengthening harmony and handling religious conflicts. The Religious Harmony Forum (FKUB) promotes religious harmony, a grant program to accommodate the needs of religious groups, a supportive and open-minded Mayor, cultural and religious festivals, successful resolution of religious conflict, and intensive dialogue between religious leaders.